Strengthening the ATO's Existing Governance Framework - Is the Proposed Tax System Advisory Board the Answer? - Pinto, Dale (Taxation Institute of Australia, 2012)
One of the issues examined at the Tax Forum that was held in Canberra in October 2011 was whether there are better ways that institutional arrangements for the tax system can be used to improve taxpayers' experiences of the tax system. The Assistant Treasurer acknowledged during a speech he gave at the Forum that the Australian Taxation Office ('ATO') is considered a 'world leader' in tax administration but went on to state that it was crucial that the ATO as the keystone of the tax system can continue to meet the challenges of the tax system now and into the future. It is in this context that he proceeded to announce that it was the Government's belief that a Tax System Advisory Board ('Advisory Board') could add value to the administration of the tax system and enhance the reputation of the ATO as a world leading administration. This paper analyses whether the proposed Advisory Board could provide the answer to strengthening the ATO's existing governance framework. It will undertake this analysis in four parts. Part one of the paper will explain the background to the Advisory Board proposal which provides the necessary context for the ensuing discussion and analysis. Part two will examine the current governance framework of the ATO, including a discussion of possible limitations of this framework. This will be followed by an examination of the case for reform in part three of the paper which will include a review of the national and international literature related to governance arrangements for tax administrations. Part four will then draw some conclusions.